The Inkwell Chronicles: The the Ink of Elspet - Book 1 - Peabody, J. D. (Nashville, Tennessee : WorthyKids, 2022)
When eleven-year-old Everett and his little sister Bea discover a curious pen, its enchanted ink leads them to a magical world, where they must find and protect the last Inkwell and save their missing father, but to do so, Everett must tap into the most magical power of all--his courage.
Keywords: Magic -- Juvenile fiction; Ink -- Juvenile fiction; Siblings -- Juvenile fiction; Missing persons -- Juvenile fiction; Magic -- Fiction; Ink -- Fiction; Brothers and sisters -- Fiction; Missing persons -- Fiction; Fantasy; Fantasy fiction